Papaya Extract and Iron Folate Capsules on Hb and Ferritin Level in Adolescent Girls with Anemia at SMA Negeri 3 Kendari City - Sultan Akbar Toruntju; Zakaria Zakaria; Roqifoh Roqifoh; Kameriah Gani (Jurnal Kesehatan Manarang, 2023)
To assess the effect of sea rabbit capsules, papaya fruit juice and iron-folate capsules on Hb and ferritin levels in high school adolescent girls with anemia. Pre-post quasi experiment was used. Location at SMA Neg 3 Kendari. The sample count is 27.6 rounded up to 30 people. The number of treatment samples was 30 people and 20 people as controls. Administered 1 time/day, for 4 weeks Sept 2022. The intervention was carried out in the school room during the break after lunch. Give capsule A to the intervention group, capsule B to the control group. The dose of capsule A is 15 mg/day, and the dose of capsule B is iron 15 mg/day and folate 300 mcg/day. There were 98 participants in the screening, 33.3% suffering from anemia, 48.9% nutritional status Chronic Energy Deficiency. There was an average increase in hemoglobin levels in the five groups, between before and after treatment, but the increase was very small, not statistically significant, p<0.05. The same thing with serum ferritin, all treatment groups and control groups experienced an increase between before and after treatment, but the value was very small or not significant (p<0.05). The results of the ANOVA test showed that there was no difference in the average hemoglobin and ferritin levels between groups, the significant level (p) = 0.37 or > α = 0.05.There was no difference in hemoglobin levels and serum ferritin levels between before and after treatment, both in the treatment group and in the control group.